Metal burial: Understanding caching behaviour and contact material culture in Australia's NE Kimberley. (February 2021) - Harper, Sam; Waina, Ian; Chalarimeri, Ambrose; Ouzman, Sven; Porr, Martin; Heaney, Pauline; Veth, Peter; Akerman, Kim; ,
This paper explores identity and the recursive impacts of cross-cultural colonial encounters on individuals, cultural materials, and cultural practices in 20th-century northern Australia. We focus on an assemblage of cached metal objects and associated cultural materials that embody both Aboriginal tradition and innovation. These cultural materials were wrapped in paperbark and placed within a ring of stones, a bundling practice also seen in human burials in this region. This 'cache' is located in close proximity to rockshelters with rich, superimposed Aboriginal rock art compositions. However, the cache shelter has no visible art, despite available wall space. The site shows the utilisation of metal objects as new raw materials that use traditional techniques to manufacture a ground edge metal axe and to sharpen metal rods into spears. We contextualise these objects and their hypothesised owner(s) within narratives of invasion/contact and the ensuing pastoral history of this region. Assemblage theory affords us an appropriate theoretical lens through which to bring people, places, objects, and time into conversation.